PENENTU AWAL WIRAUSAHA SALAH SATUNYA ADALAH ANALISA PASAR DI GORONTALO - Saleh Modjo, Ardiyanto (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2023)
Market analysis is one of the weapons as well as a shield for entrepreneurs, so that their businesses have resilience against competition. Market analysis will be the "spy" for entrepreneurs without time limits to make their entrepreneurship very flexible towards changes in the market, so that they can avoid losses, especially the more fatal one, bankruptcy. Based on this, the author is willing to collaborate with the Government of Gorontalo Province and CIDA Canada in equipping the community engaged in entrepreneurship through the cooperative and industrial service, to train knowledge and skills in market analysis. It is hoped that through this training, many business actors and those starting businesses in Gorontalo Province will have resilience against losses, especially bankruptcy.